2021
DOI: 10.1007/s11033-021-06411-z
|View full text |Cite
|
Sign up to set email alerts
|

Transferability and characterization of microsatellite markers from Byrsonima cydoniifolia A. Juss. (MALPIGHIACEAE) in seven related taxa from Cerrado biome reveal genetic relationships

Abstract: Byrsonima Rich. is one of the largest genera of the Malpighiaceae family, with 97 species occurrence in Brazil. In this study, 17 microsatellite markers previously developed and characterized in Byrsonima cydoniifolia A. Juss. were tested for seven related taxa. All species tested here are native to Brazil, and of these species four are endemic. Cross-ampli cation as successfully optimized with high e ciency for all species. Microsatellite markers panels ranged from 11 (64,8%) transfered markers in B. viminifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Cross-taxa transferability enables the development of microsatellite markers, based on markers from related species, at low cost ( Kalia et al, 2011 ; Bernardes et al, 2021 ). In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-taxa transferability enables the development of microsatellite markers, based on markers from related species, at low cost ( Kalia et al, 2011 ; Bernardes et al, 2021 ). In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers are simple sequence repeats of highly polymorphic and codominant DNA motifs (n could range from 8 to 50) that are widely distributed throughout the genomes of eukaryotes and are widely used for different population genetic studies in many different species, such as genetic diversity [ 27 , 28 , 29 ], population structure, parentage determination [ 30 , 31 , 32 ], and constructing genetic linkage maps [ 33 , 34 , 35 , 36 , 37 ], animal identification, meat traceability [ 38 , 39 ] and animal breeding [ 40 , 41 ]. Studies on related aquatic species with highly duplicated genomes have demonstrated that microsatellites derived from transcriptomes are significantly more effective than those developed from the genome using traditional methods [ 42 ].…”
Section: Introductionmentioning
confidence: 99%